Geneologi Segregasi Pendidikan Pondok Pesantren: Genealogy of Educational Segregation in Islamic Boarding Schools - Dyah Nawangsari (Fenomena, 2007)
Educational segregation is an almost obligatory phenomenon and a distinctive feature of traditional Islamic education in Indonesia, yet its underlying rationales and impacts on equitable access to knowledge remain underexamined. This study aims to trace the genealogy of educational segregation, focusing on the intellectual backgrounds, forms of segregation, and its effects on students’ social behavior at Pesantren As-Sunniyah Kencong Jember. Using a qualitative phenomenological and historical approach, data were collected through in-depth interviews, participant observation, and documentation. The findings reveal that segregation is driven by normative demands, the preservation of pesantren identity, the maintenance of spiritual purity, and perceived differences in learning abilities between male and female students. Forms of segregation include the physical separation of learning and dormitory spaces, gender-based teacher selection, and differentiated curricula and learning targets. The positive impacts of segregation outweigh the negative ones, particularly in enhancing learning concentration and post-pesantren social adaptation, while negative effects are limited to students who do not complete their studies. This study recommends a critical evaluation of segregated curricula to prevent the reinforcement of gender-based knowledge inequality. Segregasi pendidikan di pesantren merupakan fenomena yang hampir wajib dan menjadi ciri khas sistem pendidikan Islam tradisional di Indonesia, namun akar pemikiran serta dampaknya terhadap kesetaraan akses pengetahuan masih belum banyak dikaji secara kritis. Penelitian ini bertujuan menelusuri genealogi segregasi pendidikan dengan fokus pada latar belakang pemikiran, bentuk-bentuk segregasi, serta dampaknya terhadap perilaku sosial santri di Pondok Pesantren As-Sunniyah Kencong Jember. Menggunakan pendekatan kualitatif fenomenologis dan historis, data dikumpulkan melalui wawancara mendalam, observasi partisipan, dan dokumentasi. Hasil penelitian menunjukkan bahwa segregasi dilatarbelakangi oleh tuntutan normatif, pertahanan identitas pesantren, pemeliharaan kesucian hati, serta perbedaan kemampuan belajar antara santri putra dan putri. Bentuk segregasi mencakup pemisahan fisik ruang belajar dan asrama, seleksi pengajar berbasis gender, serta perbedaan kurikulum dan target capaian pembelajaran. Dampak positif segregasi lebih dominan, terutama dalam meningkatkan konsentrasi belajar dan kemudahan adaptasi sosial pasca-pesantren, sementara dampak negatifnya terbatas pada santri yang tidak menyelesaikan pendidikan. Penelitian ini merekomendasikan evaluasi terhadap kurikulum tersegregasi agar tidak memperkuat ketimpangan akses ilmu pengetahuan antargender.